Gender and sexuality: influences in the prevention of stds/aids and the contributions for nursing - Graciela Dutra Sehnem; Joice Moreira Schmalfuss; Priscila de Oliveira Bolzan Bonadiman; Fabiani Weiss Pereira; Jussara Mendes Lipinski; Lisiani Bogorni (Universidade Federal de Santa Maria, 2015)
10.5902/2179769212408 Objective: to raise awareness about how the constructions of gender and sexuality influence the prevention of the STDs/AIDS. Method: exploratory, descriptive field research with a qualitative approach. Twelve women assisted at a Basic Health Unit in Uruguaiana/RS were interviewed between September and October 2012. The data was submitted to thematic content analysis. Results: the category "The construction of being a woman and its repercussions in the prevention of STDs/AIDS" showed the necessity to promote gender equality, considering the planning of actions which aim to reduce the vulnerabilities in women's health. The category "Female sexuality: repercussions in the prevention of STDs/AIDS" showed the sexuality not only as related to purely biological sexual activity, but also understood as an idea of body, relationships, feelings and respect. Final considerations: Nursing plays a fundamental role in health education and in the contribution to the process of women empowerment in relation to their health.